Functional nanomaterials for enhanced tumor photothermal therapy - the mechanisms and applications - Han, Xiaoling; Feng, Guohai; Li, Xiaoman; Mo, Shuyi; Xu, Caijing; Yan, Jiahui; Yu, Li; Zhang, Rong; Jin, Ying; Xiao, Xiao; Deng, Li (Frontiers in Pharmacology, 2025)
Photothermal therapy (PTT) offers revolutionary breakthroughs in tumor treatment due to its minimally invasive nature, high selectivity and efficiency. Photothermal therapy is a method of using laser irradiation (near-infrared light) to convert light energy into heat, reaching a relatively high temperature to kill tumor cells. Efficient and stable photothermal conversion materials are the key factors in PTT. There are inorganic and organic nanomaterials used in photothermal therapy. Through chemical modification of them, the functions of targeted drug delivery and combination therapy can be achieved. This work generalizes the features, excellent performance and therapeutic effects of photothermal conversion nanomaterials such as polydopamine (PDA), semiconductor nanoparticles (SNPs), Au nanomaterials, palladium nanosheets (PdNs), and carbon nanomaterials. Their functions and the advantages in photothermal therapy, tumor targeting and inactivation, and the mechanisms of nanophotothermal therapy are summarized. By continuously improving the performance and treatment methods of nanomaterials, more efficient, safe and minimally invasive solutions for tumor treatment are expected.